Analisis Pemahaman Konsep Matematis Mahasiswa Statistika Pendidikan Prodi Pendidikan Ekonomi Pada Tahun Ajaran 2021/2022 - Candra Abdillah; Purwati Yuni Rahayu (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2021)
Education Statistics is a subject that is not easily mastered by Economics Education students. This study aimed to analyze the level of understanding of mathematical concepts of Education Statistics students in Economics Education Study Program. The research applied a descriptive qualitative approach. The research sample was the fourth semester students of the UNPAM Economic Education study program in the Odd semester of the 2021/2022 academic year. Data were collected by using essay test and observation techniques. Data were analyzed by descriptive statistics. The results of the analysis of each indicator of understanding mathematical concepts were: (1) re-explaining the concepts and formulas of the material to get the medium category; (2) categorizing the types of statistics used based on the questions to get a medium category; (3) calculating the required prerequisites through SPSS to get a low category; and (4) applying SPSS according to the type of statistics used to get the medium category. So it can be concluded that the level of understanding of mathematical concepts of Education Statistics students in the Economic Education study program in the 2021/2022 academic year was classified as moderate.